Association Between Impaired Myocardial Flow Reserve on 82Rubidium Positron Emission Tomography Imaging and Adverse Events in Patients With Autoimmune Rheumatic Disease. (September 2021) - Feher, Attila; Boutagy, Nabil E.; Oikonomou, Evangelos K.; Liu, Yi-Hwa; Miller, Edward J.; Sinusas, Albert J.; Hinchcliff, Monique
Abstract : Background: Coronary microvascular dysfunction has been described in patients with autoimmune rheumatic disease (ARD). However, it is unknown whether positron emission tomography (PET)-derived myocardial flow reserve (MFR) can predict adverse events in this population. Methods: Patients with ARD without coronary artery disease who underwent dynamic rest-stress 82 Rubidium PET were retrospectively studied and compared with patients without ARD matched for age, sex, and comorbidities. The association between MFR and a composite end point of mortality or myocardial infarction or heart failure admission was evaluated with time to event and Cox-regression analyses. Results: In 101 patients with ARD (88% female, age: 62±10 years), when compared with matched patients without ARD (n=101), global MFR was significantly reduced (median: 1.68 [interquartile range: 1.34–2.05] versus 1.86 [interquartile range: 1.58–2.28]) and reduced MFR (<1.5) was more frequent (40% versus 22%). MFR did not differ among subtypes of ARDs. In survival analysis, patients with ARD and low MFR (MFR<1.5) had decreased event-free survival for the combined end point, when compared with patients with and without ARD and normal MFR (MFR>1.5) and when compared with patients without ARD and low MFR, after adjustment for the nonlaboratory-based Framingham risk score, rest left ventricular ejection fraction, severe coronary calcification, and the presence of medium/large perfusion defects. In Cox-regression analysis, ARD diagnosis and reduced MFR were both independent predictors of adverse events along with congestive heart failure diagnosis and presence of medium/large stress perfusion defects on PET. Further analysis with inclusion of an interaction term between ARD and impaired MFR revealed no significant interaction effects between ARD and impaired MFR. Conclusions: In our retrospective cohort analysis, patients with ARD had significantly reduced PET MFR compared with age-, sex-, and comorbidity-matched patients without ARD. Reduced PET MFR and ARD diagnosis were both independent predictors of adverse outcomes. Abstract : Supplemental Digital Content is available in the text.